Konsep Diri Dan Kecerdasan Emosional Terhadap Perilaku Prososial Remaja Sekolah Menengah Atas - Ayu Ratna Tri Utari; I Made Rustika (Faculty of Ushuluddin and Humanities, 2020)
Prosocial behaviour is the form of behaviour that benefit others in the sense of material, physical and psychological, which is done on its own initiative without any specific motives. Prosocial behaviour is important for adolescents because of the need to be accepted by their social environment. The purpose of the study was to gather information regarding the role of self concept and emotional intelligence towards prosocial behaviour of adolescents. The subjects in this research is adolescents which currently are studying in senior high school in Denpasar. The sample consists of 107 people. The results of multiple regression test shows that self concept and emotional intelligence has a role towards prosocial behaviour of adolescents by 37,7% with significance of 0,000 (p<0,05).